PENERAPAN BADAN LAYANAN UMUM DAN IMPLIKASINYA BAGI PENGELOLAAN TAMAN NASIONAL MANDIRI YANG BERKELANJUTAN - Desi Indriani; Sambas Basuni; Bambang Supriyanto (Media Konservasi, 2013)
The Strategic Plan of the Ministry of Forestry for the period of 2010-2014 has mandated the revitalization of 12 national parks to become Public Service Agencies.  It would allow national parks to be self-financed.  Unfortunately, efforts which have been made have not shown an encouraging progress yet.  This research aims : (1) to identify the elaboration of main tasks and functions of national park, (2) to analyze the accuracy of the implementation of the Public Service Agency to the national park management, and (3) to formulate implications for the implementation of Public Service Agency to the Sustainable Self Financed National Parks management. The result shows that the elaboration of 8 out of 10 main tasks and functions of national park provide goods and services to the public and its performance can be promoted through Public Service Agency, while the other 2 are identified as government liabilities. The implementation of Public Service Agency models for Self-Financed National Park Manegement both at KNPO dan BTS NGPO meets the requirement substantially and technically. Furthermore, the KNPO Cost Benefit Ratio projection of 6 main tasks and functions for the coming 5 years shows the feasibility.  It can be concluded that national park can be self-financed through the implementation of Public Service Agency scheme. Therefore, it is suggested that in order to implement self-financed national park through Public Service Agency scheme, business development must be included as one of the main tasks and functions and its organization structure and management must be adjusted. Keywords: self-financed national park, public service agency, bromo tengger semeru national park, komodo national park